Loyal dissent: memoir of a Catholic theologian - Curran, Charles E. (Moral traditions series, 2006)
"Engrossing, enlightening, salted with humor, poignant, and profoundly inspiring, this memoir recounts the journey of one of the leading theologians of the Catholic Church in this country." Elizabeth A. Johnson, C. S. J., Distinguished Professor of Theology, Fordham University